SOUTH KOREA'S DIGITAL DIPLOMACY IN THE ERA OF THE INDUSTRIAL REVOLUTION (CASE STUDY: SOUTH KOREA INFLUENCED INDONESIA) - cifebrima suyastri (Journal of Diplomacy and International Studies, 2019)
Industry 4.0 is about the fourth industrial revolution. The industrial revolution has changed the way humans work into automation / digitalization through innovations. Its existence offers a lot of potential and can produce an opportunity in the development of the industrial sector. Human resources needed by the industry today are those who have competence in the use of digital technology. Hallyu successfully brought an improvement to the economy and image of Korea in the international eyes. Starting from the many media that aired dramas. In the drama series the soundtrack is usually song by Korean singers who are not infrequently also members of one of the idol groups there. The development of Indonesian K-pop music is also like a domino effect. in Indonesia itself appeared several Boyband and Girlband in the style of South Korea which had raised its own pro and contra in Indonesia. Musicians in Indonesia spoke up about the problem. The existence of Boyband-Girlband in Indonesia is considered to beat the band which is the hallmark of music in Indonesia. The development of South Korean culture and the existence of digital diplomacy they can easily promote their products via the internet such as YouTube, Instagram, Facebook, Twitter etc. In this case, Researchers used a qualitative descriptive method by describing the results of research that has been done by researchers. The study was conducted by reviewing documentation, books, and data related to the research theme.